Investigation of microbial community changes in petroleum polluted sediments during hydrocarbons degradation. Issue 2 (17th February 2022) - Mahjoubi, Mouna; Cappello, Simone; Santisi, Santina; Najjari, Afef; Souissi, Yasmine; Cherif, Ameur
ABSTRACT: Bioremediation is among the most basic and reliable way to eliminate pollutants by transforming the toxic petroleum components into less toxic metabolites. In order to compare the change of bacterial community during oil-biodegradation process, two oil-polluted sediments sampled from Tunisia were analyzed using 16S rDNA clone libraries. During the experimental period, measurements of microbial abundance along with qualitative and quantitative analysis of pollutants were carried out. Fingerprinting analysis of natural samples showed the presence of different classes of bacteria with the dominance of Gammaproteobacteria (>60%). The bacterial diversity decreased in enrichment cultures with crude oil with the appearance and predominance of Alcanivorax spp . Our data also showed that several Obligate Marine Hydrocarbonoclastic Bacteria (OMHB: Alcanivorax, Cycloclasticus and Marinobacter) were stimulated by the addition of petroleum. The shift of diversity and the dominance of OMHB were associated with high degradation rate of crude oil (the total degradation of petroleum TERHCs was estimated at 90% and 70% in TST1E and TST2E) and a decrease in sediment toxicity to Corophium orientale . Since several factors can influence the clean-up in-field, the effectiveness of biostimulation treatment and its optimization at lab scale under controlled conditions would facilitate and allow the application in-situ. Moreover, the study of the community diversity allows the detection and the identification of the dominant hydrocarbonoclastic species such as Alcanivorax which it would be beneficial in future experiments to facilitate the selection of the autochthonous strains (adapted to support the contamination) for the reconstruction of efficient consortia useful in the cleanup of hydrocarbon contaminated sites.